2019
DOI: 10.1021/acs.analchem.9b01111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Liquid Surface Enhanced Raman Scattering Platform Based on Soft Tubular Microfluidics for Label-Free Cell Detection

Abstract: Cell detection is of great significance for biomedical research. Surface enhanced Raman scattering (SERS) has been widely applied to the detection of cells. However, there is still a lack of a general, low-cost, rapid, and sensitive SERS method for cell detection. Herein, a dynamic liquid SERS platform, which combines label-free SERS technique with soft tubular microfluidics for cell detection, is proposed. Compared with common static solid and static liquid measurement, the dynamic liquid SERS platform can pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Microfluidic platforms can precisely control over fluid flow in the microchannels [18]. Microfluidic chips have synthesized nano/micro-hydrogels, which have a wide range of biological and medical applications, such as enzyme-catalyzed reactions [19], cell manipulation [20], tumor screening [21] and microparticle synthesis [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic platforms can precisely control over fluid flow in the microchannels [18]. Microfluidic chips have synthesized nano/micro-hydrogels, which have a wide range of biological and medical applications, such as enzyme-catalyzed reactions [19], cell manipulation [20], tumor screening [21] and microparticle synthesis [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have alternatively focused on dynamic liquid SERS substrates such as SERS‐integrated microfluidic systems, where analytes encounter the SERS substrate with a higher frequency than in conventional static liquid systems. [ 7–10 ] Therefore, more reliable and reproducible Raman signals can be achieved for analytes with low concentrations. Such microfluidic SERS systems are further advantageous because analytes can be detected in a closed polydimethylsiloxane (PDMS) device, in the volume as small as a few nanoliters, which also prevents the contamination by harmful substances during measurements.…”
Section: Figurementioning
confidence: 99%
“…Si wafer, and static liquid SERS in quartz capillary, Xu et al [4] demonstrated the superiority of microfluidic approach for rapid, sensitive, and repeatable SERS analysis. Due to the unique advantages of rapid, efficient, flexible operation for small volume fluids, microfluidics has been applied in SERS for more than 20 years.…”
Section: Introductionmentioning
confidence: 99%